Truth and justice - Michaels, Fern (Michaels, Fern. Sisterhood, 2020)
"When Alexis Thorn encounters a distraught young woman, Bella Nolan, alone in a restaurant, crying instead of eating, she offers comfort and soon uncovers a mission that will require the very particular skills of the Sisterhood. Alexis learns that the woman's husband was recently killed in action in Afghanistan. Before he reported for duty, they took steps to preserve their chances of having children. But when Bella visits the fertility clinic, she discovers her eggs are no longer there and the circumstances are beyond suspicious. Heartbroken at this tale of shattered hopes, Alexis recruits the Sisterhood to investigate. Soon, the uncover a con artist on an obsessive mission."--Provided by publisher.